CHATGPT-SUPPORTED PROJECT-BASED LEARNING IN DEVELOPING MOTIVATION, CRITICAL THINKING, AND POETRY APPRECIATION SKILLS - Muhammad Arief Budiman; Rakhimov Kholmurot Abdullayevich; Ikha Listyarini; Munifatul Nisa; Nabil Kholisatunnajah; Nafira Zahwa Aulia; Natasya Agustina Madiyani (ELEMENTARY: Jurnal Inovasi Pendidikan Dasar, 2026)
The rapid development of generative artificial intelligence offers new opportunities for enhancing project-based learning in teacher education. This study aims to examine the impact of ChatGPT-assisted Project-Based Learning (PBL) on learning motivation, writing anxiety, critical thinking skills, and poetry appreciation among pre-service elementary teachers. A quasi-experimental pretest–posttest control group design was employed involving 171 undergraduate students enrolled in a Children’s Literature Appreciation course. The experimental group participated in ChatGPT-assisted PBL, while the control group engaged in conventional PBL. Data were collected using the L2 Motivational Self System (L2MSS) questionnaire, the Second Language Writing Anxiety Inventory (SLWAI), and analytic rubrics for critical thinking and poetry appreciation. Data were analyzed using descriptive and inferential statistics. The results indicate that students in the ChatGPT-assisted PBL group demonstrated higher learning motivation and critical thinking skills, as well as lower levels of writing anxiety compared to those in the control group. The integration of ChatGPT provided scaffolding support in idea generation, diction selection, and reflective revision, which enhanced students’ confidence and engagement in poetry learning. These findings suggest that AI-assisted PBL can serve as an effective pedagogical strategy to improve both cognitive and affective learning outcomes in teacher education. ABSTRAK Perkembangan kecerdasan buatan generatif membuka peluang baru dalam inovasi pembelajaran berbasis proyek di pendidikan guru. Penelitian ini bertujuan menganalisis pengaruh Project-Based Learning (PBL) berbantuan ChatGPT terhadap motivasi belajar, kecemasan menulis, keterampilan berpikir kritis, dan kemampuan apresiasi puisi mahasiswa calon guru sekolah dasar. Penelitian menggunakan desain kuasi-eksperimental dengan model pretest–posttest control group yang melibatkan 171 mahasiswa pada mata kuliah Apresiasi Sastra Anak. Kelompok eksperimen mengikuti PBL yang terintegrasi dengan ChatGPT, sedangkan kelompok kontrol menggunakan PBL konvensional. Data dikumpulkan melalui kuesioner L2 Motivational Self System (L2MSS), Second Language Writing Anxiety Inventory (SLWAI), serta rubrik penilaian berpikir kritis dan apresiasi puisi. Analisis data dilakukan menggunakan statistik deskriptif dan inferensial. Hasil penelitian menunjukkan bahwa mahasiswa pada kelompok PBL berbantuan ChatGPT memiliki motivasi belajar dan keterampilan berpikir kritis yang lebih tinggi serta tingkat kecemasan menulis yang lebih rendah dibandingkan dengan kelompok kontrol. Integrasi ChatGPT memberikan dukungan scaffolding dalam pengembangan ide, pemilihan diksi, dan proses refleksi, sehingga meningkatkan keterlibatan dan kepercayaan diri mahasiswa dalam pembelajaran puisi. Temuan ini menunjukkan bahwa integrasi AI dalam PBL dapat menjadi strategi pedagogis yang efektif untuk meningkatkan kemampuan kognitif dan afektif dalam pendidikan guru.